2023
DOI: 10.2147/vhrm.s416967
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Distribution Patterns of Peripheral Arterial Disease According to Patient Characteristics: A Unicentral Cohort Study

Abstract: Peripheral arterial disease (PAD) is a common disease with multiple risk factors and affects patients worldwide. Several international studies have established correlations between anatomical topography/distribution of atherosclerosis and comorbidities in patients with PAD. In this cohort study, we aimed to analyze the patterns of atherosclerosis (site, distribution, and degree) in patients who underwent lower limb computed tomography angiography and arterial angiography by identifying the atherosclerotic plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In patients with DM, the intermediate part was the site most involved in upper extremity PAD; this is consistent with the observation made by Alghanimi et al that the femoropopliteal segment is the site most involved in PAD in patients with DM. 25 The present study found that PAD coexisting with HTN and DM likely manifests in a stenotic form rather than as an occlusive disease.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In patients with DM, the intermediate part was the site most involved in upper extremity PAD; this is consistent with the observation made by Alghanimi et al that the femoropopliteal segment is the site most involved in PAD in patients with DM. 25 The present study found that PAD coexisting with HTN and DM likely manifests in a stenotic form rather than as an occlusive disease.…”
Section: Discussionsupporting
confidence: 46%
“…This study is a continuum sub-study of another observational cohort study conducted by Alghanimi et al on lower extremity involvement and anatomical distribution of PAD with different comorbidities in the Saudi population (2023). 25 The present study focused on elucidating the relationship between anatomical sites or distribution patterns in upper extremity PAD and the associated risk factors and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation